2021
DOI: 10.3390/foods10020208
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Digital Technologies for Purchasing and Consumption in Urban and Regional Agro-Food Systems: A Systematic Review

Abstract: The use of digital technologies in the agro-food sector is growing worldwide, and applications in the urban and regional food systems represent a relevant segment of such growth. The present paper aims at reviewing the literature on which and how digital technologies support urban and regional agro-food purchasing and consumption, as well as their characteristics. Data collection was performed on Scopus and Web of Science. Articles were selected using a research string and according to specific inclusion and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The FAO argued that digital technologies at the farm level, such as sensors, robots, and drones, can provide precise information to farmers and help them increase yields in a climate-friendly way. Blockchain technology can enhance traceability and sustainability by monitoring the food chain from the field to the final consumer [97]. The United Nations also explored the opportunities offered by digital technologies in the field of nutrition and concluded that they help provide tailored health advice but warned against their potential threats to the privacy of health information [98].…”
Section: Emerging Transition Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The FAO argued that digital technologies at the farm level, such as sensors, robots, and drones, can provide precise information to farmers and help them increase yields in a climate-friendly way. Blockchain technology can enhance traceability and sustainability by monitoring the food chain from the field to the final consumer [97]. The United Nations also explored the opportunities offered by digital technologies in the field of nutrition and concluded that they help provide tailored health advice but warned against their potential threats to the privacy of health information [98].…”
Section: Emerging Transition Pathwaysmentioning
confidence: 99%
“…The FAO argued that "digital technologies can trigger major changes or "disruptions" in the sustainable food system that not only improve efficiency and speed but also redistribute information and power along the value chain" [99]. A similar approach was adopted by the European Commission, which, albeit recognizing the limited spread of digital technologies across the Union, considers them capable of increasing sustainability in the agro-food system [100], thus prioritizing digitalization in the Common Agricultural Policy (CAP) reform 2021-2027 [97,101].…”
Section: Emerging Transition Pathwaysmentioning
confidence: 99%
“…Financial information exchange; external factors; big data analysis capability; IoT and system integration; collaboration; real-time quality information; risks reduction; transparency; automation; traceability; forecasts; accessibility; data collection-storage-recall; supplier information; sustainability information; supply forecasting and planning (Samoggia et al, 2021) Digital platforms for procurement in food supply chains.…”
Section: Digital Platforms In Food Supply Chainsmentioning
confidence: 99%
“…Nowadays, the municipalities in various countries, especially in Europe and North America, officially recognize the importance of urban agriculture in their urban planning and food policy documents to ensure sustainable development and better city life with a quality environment (Cretella and Buenger 2016). UN-FAO launched the City Region Food Systems (CFRS) Programme intending to boost rural-urban interactions to enhance the regional agro-food system, and Milan Food Policy Pact makes a forum of 240 cities around the world to share urban food policies and strengthen the local food system (Samoggia et al, 2021). Table 2 illustrates international examples of policy and good practice against current ones in Bangladesh According to another city resident interviewed:…”
Section: Institutional Framework Toward Rooftop Gardening In Differen...mentioning
confidence: 99%